Efficacy and safety assessment of acupuncture and nimodipine to treat mild cognitive impairment after cerebral infarction: a randomized controlled trial. Issue 1 (December 2016) - Wang, Shuhua; Yang, Hongling; Zhang, Jie; Zhang, Bin; Liu, Tao; Gan, Lu; Zheng, Jiangang
Abstract Background Cerebral infarction frequently leads to mild cognitive impairment (MCI). Prompt management of MCI can prevent vascular dementia and improve patient outcome. This single center randomized controlled trial aims to investigate the efficacy and safety of acupuncture and nimodipine to treat post-cerebral infarction MCI. Methods A total of 126 Chinese patients with post-cerebral infarction MCI recruited from the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine between April 2013 and June 2014 were randomized at 1:1: 1 ratio into nimodipine alone (30 mg/time and 3 times daily), acupuncture alone (30 min/time, 6 times/week), and nimodipine + acupuncture groups. The treatments were 3 months. Cognitive function was evaluated using Montreal Cognitive Assessment (MoCA) scale at enrollment interview, at the end of 3-month therapy, and at the post-treatment 3-month follow-up. Results The per-protocol set included 39, 40, and 40 patients from nimodipine alone, acupuncture alone, and the combination group, respectively, was analyzed. Intra-group comparison revealed that MoCA score at the follow-up improved significantly by 15.8 ± 10.9, 20.9 ± 13.8 %, and 30.2 ± 19.7 % compared with the baseline MoCA for nimodipine alone, acupuncture alone, and the combination group, respectively. Inter-group comparison demonstrated that the combination therapy improved MoCA score (5.5 ± 2.2) at significantly higher extent than nimodipine alone (3.1 ± 1.8) and acupuncture alone (4.3 ± 2.3) at the follow-up (AllP  < 0.05), and significantly higher proportion of patients in acupuncture alone group (80 %) and the combination therapy group (90 %) than in nimodipine alone group (56.4 %) showed ≥12 % MoCA score improvement compared with the baseline MoCA (AllP  < 0.05). No adverse event was reported during the study. Conclusion Acupuncture may be used as an additional therapy to conventional pharmacological treatment to further improve the clinical outcomes of patients with post-cerebral infarction MCI. Trial registration The study was registered at the Chinese Clinical Trial Registry (http://www.chictr.org.cn/, Unique Identifier:ChiCTR-IOR-15007366 ). The date of registration is November 4, 2015.